Indium-zinc-based alloy anodes forming porous structures for aqueous zinc batteries
Patent Information
- Application Number
- JP2024552192
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-04
- Filing Date
- 2023-03-02
- Publication Date
- 2025-03-13
AI Technical Summary
【0012】 本開示の前述のおよび他の目的、特徴、および利点は、添付の図面を参照して進められる以下の詳細な説明からさらに明らかとなる。
Smart Images

Figure 2025506966000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of the earlier filing date of U.S. Provisional Application No. 63 / 316,578, filed March 4, 2022, which is incorporated by reference herein in its entirety.
[0002] Acknowledgement of government support This invention was made with Government support under Contract DE-AC0576RL01830 awarded by the U.S. Department of Energy. The Government has certain rights in this invention.
[0003] Field The present disclosure relates to indium zinc based alloy anodes for aqueous zinc batteries. [Background technology]
[0004] background Aqueous zinc batteries use earth abundant elements, are safe, low cost, and have established recyclability. Zinc-based batteries (e.g., MnO2 / Zn) have been commercialized as primary batteries and are one of the leading technologies in the battery market. However, the rechargeability of MnO2 / Zn and other zinc-based batteries is severely limited due to challenges with the zinc anode, especially under conditions of high depth of discharge and / or high plating current density. Zinc dendrite formation resulting in internal short circuits is the most common cause of cell failure in aqueous zinc batteries with non-alkaline electrolytes. There is a need for zinc anodes that exhibit reduced dendrite formation during cycling. Summary of the Invention [Means for solving the problem]
[0005] overview Anodes for aqueous zinc batteries are disclosed. Batteries including the anodes, as well as methods of making and using the anodes, are also disclosed.
[0006] The disclosed anode embodiments include Inx M y Zinc z alloy, where M is Al, Ag, Bi, Pb, Sn, Cd, or any combination thereof. In some embodiments, M is Al. In some aspects, if the anode has not been previously cycled, the following applies: x is in the range of 0.03-0.2, z is in the range of 0.80-0.97, x+y+z=1, and the anode is In x M y Zinc z The alloy includes indium and zinc domains distributed throughout the alloy, with the exposed top surface of the anode having a zinc concentration of ≧z. It is understood that the values of x, y, and z also correspond to the atomic percentage of each element in the alloy. For example, a value of x=0.08 corresponds to 8 at% indium. Thus, the composition In 0.1 Al 0.01 Zinc 0.89 An indium-aluminum-zinc alloy having the formula (I) contains 10 at.% indium, 1 at.% aluminum, and 89 at.% zinc.
[0007] In some aspects, the anode further comprises a current collector. In certain embodiments, the anode further comprises a zinc layer having a thickness in the range of 0.5 μm to 1 μm in contact with the current collector, and / or an In layer proximate to the current collector. x M y Zinc z The concentration of indium in the lower region of the alloy is >x.
[0008] In any of the above or following embodiments, in a partially or fully discharged state after one or more cycles, the anode may include a porous surface portion including a plurality of pores, the porous surface portion having an indium concentration greater than x at% and a zinc concentration less than z at%, and the bulk portion having an In x M y Zinc z In a fully discharged state, the porous surface portion may include at least 50 at% indium. In some embodiments, at least some of the indium in the porous surface portion is present as In2O3.
[0009] In any of the foregoing or following embodiments, when the anode is subsequently in a partially or fully charged state, the pores of the porous surface portion are at least partially filled with zinc. In some embodiments, the morphology of the indium in the porous surface portion remains stationary as the pores are filled with zinc during the charging process and then empty during the discharging process.
[0010] An embodiment of the rechargeable zinc cell includes an anode as disclosed herein, a cathode, and an aqueous electrolyte. The aqueous electrolyte includes a zinc salt and may include one or more additives. In some embodiments, the aqueous electrolyte includes ZnSO4, Zn(H2NSO3)2, Zn(CH3SO3)2, Zn(C2F6NO4S2)2, Zn(F2NO4S2)2, Zn(ClO4)2, and Zn(CH3CO2)2, or any combination thereof.
[0011] The disclosed anode embodiment is In 3+ ions and Zn 2+ In was deposited from an aqueous solution containing In:Zn ions in the molar ratio x:z. x M y Zinc z The alloy may be formed by preparing a film comprising the alloy, which may be electrodeposited onto a current collector.
[0012] The foregoing and other objects, features, and advantages of the present disclosure will become more apparent from the following detailed description which proceeds with reference to the accompanying drawings.
[0013] BRIEF DESCRIPTION OF THE DRAWINGS The patent or application file contains at least one drawing executed in color. Copies of this patent or patent application publication with color drawing(s) will be provided by the Office upon request and payment of the necessary fee. [Brief description of the drawings]
[0014] [Figure 1]1A-1C are diagrams illustrating desirable anode properties for zinc (FIG. 1A), indium (FIG. 1B), and aluminum (FIG. 1C).
[0015] [Diagram 2] 2A and 2B are X-ray diffraction (XRD) spectra of AlZn deposited on copper (FIG. 2A) and InZn deposited on brass (FIG. 2B).
[0016] [Diagram 3] 3A-3D show scanning electron microscope (SEM) images of uncycled AlZn on Cu (FIG. 3A) and uncycled InZn on brass (FIG. 3B), as well as energy dispersive spectroscopy (EDS) mapping showing zinc and aluminum on the AlZn surface (FIG. 3C) and zinc, indium, and aluminum on the InZn surface (FIG. 3D).
[0017] [Figure 4] 4A-4C show the XRD spectrum (FIG. 4A) and SEM image (FIG. 4B) of a commercial zinc foil in its pristine state, and the SEM image of the zinc foil after the first discharge cycle of the zinc foil anode (FIG. 4C).
[0018] [Diagram 5] 5A-5D show SEM images from the analysis of post-cycled AlZn on Cu (FIG. 5A) and InZn on brass (FIG. 5B), as well as EDS mapping showing zinc and aluminum on the AlZn surface (FIG. 5C) and zinc and indium on the InZn surface (FIG. 5D).
[0019] [Figure 6] 6A-6D show SEM images from the analysis of uncycled InAlZn with 2 at% In (FIG. 6A), cycled InAlZn with 2 at% In (FIG. 6B), and EDS mapping of uncycled InZn with 2 at% In (FIG. 6C) and cycled InZn with 2 at% In (FIG. 6D).
[0020] [Figure 7] 7A-7F show cross-sectional SEM images from the analysis of uncycled InAlZn (2.3:1 Zn:In) (FIG. 7A), InAlZn (8.3:1 Zn:In) (FIG. 7B), and InAlZn (10:1 Zn:In) (FIG. 7C), as well as the corresponding EDS mappings (FIGS. 7D-7F) showing zinc, indium, and aluminum on the InAlZn surface.
[0021] [Figure 8] 8A and 8B show the SEM image (FIG. 8A) and energy dispersive X-ray (EDX) mapping (FIG. 8B) of the cycled InZn obtained from the analysis, where the inset in FIG. 8B shows the oxygen distribution along the InZn surface.
[0022] [Figure 9] 9A-9C are graphs showing the cycling of a commercial zinc foil anode (FIG. 9A), an AlZn / Cu anode (FIG. 9B), and an InZn / brass anode (FIG. 9C), each cycled at a current density of 1 mA cm-2 with a corresponding charge of 5 mAh cm-2.
[0023] [Figure 10] 10A-10C are graphs showing the cycling of a commercial zinc foil (FIG. 10A), an AlZn / Cu anode (FIG. 10B), and an InZn / brass anode (FIG. 10C), each cycled at a current density of 10 mA cm-2 with a corresponding charge of 5 mAh cm-2.
[0024] [Figure 11] 11A and 11B are graphs showing the cycling of an InZn anode containing more than 15 at.% indium (FIG. 11A) or less than 5 at.% indium (FIG. 11B) cycled at a current density of 10 mAcm with a corresponding charge of 5 mAhcm.
[0025] [Figure 12] 12A and 12B are graphs showing the first full cycle charge / discharge curves for full cells with zinc foil anodes and dibenzo[b,i]thianthrene-5,7,12,14-tetraone (DTT) cathodes using a current density of 100 mA g (FIG. 12A), and the long-term cyclability of full DTT cells with zinc foil, AlZn, or InZn anodes using a current density of 100 mA g (FIG. 12B), all cells containing an aqueous 2 M ZnSO electrolyte.
[0026] [Figure 13] 13A and 13B are SEM images resulting from analysis of the zinc powder electrode in its pristine state (FIG. 13A) and after cycling (FIG. 13B). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Detailed Description Anodes for aqueous zinc batteries are disclosed. In some embodiments, the anodes comprise In x M y Zinc z alloy, where M is Al, Ag, Bi, Pb, Sn, Cd, or any combination thereof. If the anode has not been previously cycled, x is in the range of 0.03 to 0.20, z is in the range of 0.80 to 0.97, and x+y+z=1. Batteries including the anodes, as well as methods of making and using the anodes, are also disclosed. I. Definitions and Abbreviations
[0028] The following explanations of terms and abbreviations are provided to better describe the present disclosure and guide those skilled in the art in practicing the present disclosure. As used herein, "comprising" means "including," and the singular forms "a" or "an" or "the" include plural referents unless the context clearly dictates otherwise. The term "or" refers to one element of the listed alternative elements, or a combination of two or more elements, unless the context clearly dictates otherwise.
[0029] Unless otherwise explained, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this disclosure belongs.Methods and materials similar or equivalent to those described herein can be used in the practice or testing of this disclosure, and suitable methods and materials are described below.Materials, methods, and examples are merely illustrative and are not intended to be limiting.Other features of this disclosure will be apparent from the following detailed description and claims.
[0030] The disclosure of a numerical range should be understood to refer to each individual point within that range, including the endpoints, unless otherwise specified. Unless otherwise specified, any number expressing the amount of an ingredient, molecular weight, percentage, temperature, time, etc., should be understood as being modified by the term "about" when used in this specification or claims. Thus, unless otherwise stated, implicitly or explicitly, or unless the context is properly understood by those skilled in the art to have a more determinative interpretation, the numerical parameters indicated are approximations that may depend on the desired properties sought and / or the detection limits in standard test conditions / methods known to those skilled in the art. When directly and clearly distinguishing the embodiments from the prior art discussed, the numbers of the embodiments are not approximations unless the word "about" is stated.
[0031] Although there are alternatives for the various ingredients, parameters, operating conditions, etc., set forth herein, that does not mean that the alternatives are necessarily equivalent and / or perform equally well, nor is it meant that the alternatives are listed in order of preference unless otherwise specified.
[0032] Definitions of general terms in chemistry can be found in Richard J. Lewis, Sr. (ed.), Hawley's Condensed Chemical Dictionary, published by John Wiley & Sons, Inc., 2016 (ISBN 978-1-118-13515-0). In order to facilitate review of the various embodiments of the disclosure, the following explanations of specific terms are provided.
[0033] Alloy: As used herein, the term "alloy" refers to a solid mixture of two or more metals. An alloy may be a heterogeneous mixture containing dispersed domains or regions containing one metal.
[0034] Anode: The electrode through which charge flows in a polarized electrical device. From an electrochemical standpoint, negatively charged anions migrate toward the anode and / or positively charged cations migrate away from the anode to balance the electrons that leave via the external circuit.
[0035] Cathode: The electrode through which charge flows from a polarized electrical device. From an electrochemical point of view, positively charged cations constantly move toward the cathode and / or negatively charged anions move away from the cathode to balance the electrons arriving from the external circuit.
[0036] Cell: As used herein, a cell refers to an electrochemical device used to produce a voltage or current from a chemical reaction, or the reverse, where a chemical reaction is induced by an electric current. A battery contains one or more cells. The terms "cell" and "battery" are used interchangeably when referring to a battery that contains only one cell.
[0037] Current Collector: The part of a battery that directs the flow of electrons between the electrode and the battery terminal. The current collector may also provide mechanical support for the electrode's active material.
[0038] Electrolyte: A substance containing free ions that behaves as an electrically conductive medium. Electrolytes generally contain ions in solution.
[0039] Polarization: The change in electrode potential resulting from the passage of electric current across an electrode-electrolyte interface.
[0040] Pore: one of many openings or voids in a solid substance. II. InZn-based alloy anode
[0041] Desirably, an anode for an aqueous zinc battery would provide (i) reduced zinc dendrite formation / good cycling performance, (2) improved zinc resistance to corrosion / gassing, (3) use of earth abundant elements, and / or (4) good manufacturability in an economical / scalable manner. Figures 1A-1C show certain desirable anode properties of zinc, indium, and aluminum (e.g., gassing, dendrites, manufacturing, cyclability, cost, and / or corrosion resistance), as well as their defining physicochemical properties including hydrogen exchange current density (HECD), redox potential, and / or abundance. Exchange current density is the current measured when no potential is applied to the electrode material in a given electrochemical reaction (e.g., hydrogen evolution); a low HECD may reflect a high overpotential in the hydrogen evolution reaction. Figure 1A shows that zinc foil meets the two criteria of low cost and manufacturability but falls short in other parameters.
[0042] In some embodiments of the present disclosure, In x M y Zinc z Anodes for zinc-based batteries are disclosed that include alloys, where x+y+z=1, and M is Al, Ag, Bi, Pb, Sn, Cd, or any combination thereof. It should be understood that the values of x, y, and z also correspond to the atomic percentage of each element in the alloy. For example, a value of x=0.08 corresponds to 8 at% indium. Thus, the composition In 0.1 Al 0.01 Zinc 0.89An indium-aluminum-zinc alloy having the formula (I) contains 10 at.% indium, 1 at.% aluminum, and 89 at.% zinc.
[0043] In some embodiments, M is a metal. For example, M can be Al. When M is Al, the alloy has the formula In x Al y Zinc z In certain embodiments, M is a combination of Al and one or more additional metals M, where the other metal(s) is Ag, Bi, Pb, Sn, Cd, or any combination thereof. When the alloy includes one additional metal M in addition to Al, where M is Ag, Bi, Pb, Sn, or Cd, the alloy has the formula In x Al y1 M y2 Zinc z where y1+y2=y. If the alloy contains two further metals M in addition to Al, the metals M are M 1 and M. 2 and the alloy has the formula In x Al y1 M 1 y2 M 2 y3 Zinc z Similarly, if an alloy contains three additional metals M in addition to Al, the metals M are M 1 , M 2 , and M. 3 and the alloy has the formula In x Al y1 M 1 y2 M 2 y3 M 3 y4 Zinc z where y1+y2+y3+y4=y. Or, if the alloy contains four further metals M in addition to Al, the metals M are M 1 , M 2 , M 3 , and M. 4 and the alloy has the formula In x Al y1 M 1 y2 M2 y3 M 3 y4 M 4 y5 Zinc z where y1+y2+y3+y4+y5=y. If the alloy contains five further metals M in addition to Al, the metals M are M 1 , M 2 , M 3 , M 4 , and M. 5 and the alloy has the formula In x Al y1 M 1 y2 M 2 y3 M 3 y4 M 4 y5 M 5 y6 Zinc z and y1+y2+y3+y4+y5+y6=y.
[0044] The In / Zn bond results in a positive shift in the dissolution potential of the less noble metal, facilitating the removal of the less noble component (Zn) (Erlebacher, Nature 2001, 410:450-453; Xia et al., Materials Research Bulletin 2017, 85:1-9; Aiello et al., JECS 2018, 165(14):C950-C961). Thus, zinc can be selectively dealloyed or removed from the anode upon discharge.
[0045] The dealloyed structure of the disclosed anodes can be tuned by varying the alloy composition and / or dealloying conditions. In some embodiments, the amount and distribution of indium is controlled to provide another advantage in tuning and / or inhibiting dendritization, since during the process of zinc removal that occurs during the discharge process, the remaining metals can rearrange to create a nanoporous structure with a higher surface area compared to uncycled anodes.
[0046] In one aspect, if no cycle has been performed on the anode previously, the anode on which the cycle has not been performed is In x M y Zn z and contains an alloy, where x ranges from 0.03 to 0.20, z ranges from 0.80 to 0.97, and x + y + z = 1. As shown above, M may be one metal or a combination of multiple metals. In certain embodiments, x ranges from 0.05 to 0.15 and z ranges from 0.83 to 0.97. In some embodiments, x ranges from 0.08 to 0.15 or 0.08 to 0.12, or x is within a range having endpoints selected from 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, or 0.20. In certain embodiments, z ranges from 0.83 to 0.92 or 0.86 to 0.92, or z is within a range having endpoints selected from 0.80, 0.81, 0.82, 0.83, 0.84, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, or 0.97. In any of the foregoing or following aspects, y ≤ 0.02, such as 0 < y ≤ 0.02 or 0 < y ≤ 0.01, etc., or y is within a range having endpoints selected from 0, 0.001, 0.002, 0.004, 0.006, 0.008, 0.010, 0.012, 0.014, 0.016, 0.018, or 0.02.
[0047] In any of the foregoing or following aspects, before performing the anode cycle, the anode is In x M y Zn zThe alloy may include indium and zinc domains distributed throughout (see, e.g., FIG. 3D, discussed in Example 1). As used herein, the term "domain" refers to a region or area that includes one metal. The domains may be isolated, adjacent, or a combination of isolated and adjacent domains. In some aspects, at least some of the indium domains are isolated domains and are surrounded by zinc domains. In some embodiments, the distribution of the domains is non-uniform. For example, an anode electrodeposited on a current collector may have a thin layer (e.g., in the range of 0.5 μm to 1 μm) consisting of or containing primarily zinc (e.g., at least 95 at%) in contact with the current collector (e.g., as shown in FIGS. 7D-7F, Example 1). Competitive deposition of zinc and indium then occurs. Since indium is deposited more favorably, the concentration of indium may be higher in the lower region (closer to the current collector) of the deposited zinc-rich alloy compared to the overall indium concentration of the alloy (e.g., as shown in FIGS. 7D-7F). Thus, the concentration of indium in the lower region of the anode may be >x. Also, the concentration of indium in the upper exposed surface of the uncycled anode may be ≦x, while the concentration of zinc in the upper exposed surface may be ≧z. In one example, an anode having a surface indium concentration in the range of 9.5 at% to 12 at% may have a bulk indium concentration in the range of 10 at% to 15 at%. Non-uniformity may be more pronounced at higher indium concentrations (e.g., above 15 at%; FIG. 7D) and less pronounced at lower indium concentrations (e.g., below 15 at%; FIG. 7E, 7F). The arrangement of the indium and zinc domains is not an interdigitated arrangement, with the uncycled anode having an upper indium surface with indium "fingers" extending into the bulk portion containing zinc. Instead, the upper exposed surface of the uncycled anode contains both indium and zinc and may be enriched in zinc compared to the bulk of the anode, as discussed above (see, e.g., Figures 7E, 7F).
[0048] In any of the foregoing or following embodiments, in a partially or fully discharged state after one or more cycles, the anode comprises: (i) a porous surface portion comprising a plurality of pores; and (ii) In x M y Zinc z and a bulk portion containing the alloy. The porous surface portion containing a plurality of pores is formed when zinc is dealloyed from the anode during the discharge process. Indium can remain in the surface portion as zinc is dealloyed and rearrange within the porous network, resulting in an embodiment that can include a porous surface portion having an indium concentration greater than x at% and a zinc concentration less than z at%. For example, if the anode has not previously been cycled, and x is 0.1 (10 at%), the surface portion has an indium concentration greater than 10 at% when the anode is in a partially or fully discharged state after one or more cycles. Conversely, if z is 0.9 (90 at%) for an uncycled anode, the surface portion has a zinc concentration less than 90 at% when the anode is in a partially or fully discharged state after one or more cycles. When the anode is cycled, the bulk portion can have an overall concentration of indium and zinc that remains substantially unchanged (e.g., the concentrations change by less than ±5% relative to the initial concentrations x and z). The porous surface portion may have a sponge-like morphology, for example as shown in Figure 5D (discussed in Example 1), and has an increased surface area compared to the surface area before the anode was cycled. In any of the above or following embodiments, the depth of the porous surface portion may increase as the depth of discharge of the anode increases.
[0049] In any of the foregoing or following embodiments, at least a portion of the indium in the porous surface portion may be oxidized and present in the form of In2O3. Without wishing to be bound to a particular theory of operation, it is currently believed that oxidation of the indium-rich surface may stabilize the morphology of the porous surface.
[0050] In some embodiments, when the anode is in a partially or fully discharged state, the porous surface portion comprises at least 50 at% indium. In certain aspects, when in a partially or fully discharged state, the porous surface portion comprises at least 60 at%, at least 65 at%, at least 70 at%, or at least 75 at% indium, such as 60 at% to 100 at%, 60 at% to 98 at%, 60 at% to 95 at%, 65 at% to 95 at%, 70 at% to 95 at%, or 75 at% to 95 at%, etc. The indium concentration in the surface portion may gradually increase as the anode undergoes a discharge process.
[0051] In any of the above or following aspects, the pores of the porous surface portion may be at least partially filled with zinc in a subsequent portion or in a fully charged state. In some embodiments, the pores of the porous surface portion are gradually filled with zinc as the anode undergoes a charging process. In certain aspects, the porous morphology of the indium of the surface portion remains stationary or essentially stationary as the pores are filled with zinc during the charging process and emptied again when the anode is discharged. The stationary or essentially stationary morphology can be verified by imaging, such as scanning electron microscope imaging, or any other suitable method.
[0052] In some embodiments, when x is <0.05, few or no pores are formed when the anode is discharged, and the mitigation of dendrites provided by the porous surface structure does not occur. For example, when zinc is doped with about 300 ppm (<1.7 at%) indium, the porous surface structure is not formed. In certain embodiments, when x>0.015, the surface concentration of indium is not increased at the same time (e.g., a 50% increase in indium content can only increase the surface indium concentration by 20%); however, the increase in indium concentration in the bulk portion of the anode results in poor cyclability compared to embodiments of anodes where x is in the range of 0.05-0.15.
[0053] Advantageously, some aspects of the disclosed anodes exhibit reduced dendrite formation when cycled compared to AlZn and Zn anodes. In certain embodiments, the anodes do not exhibit dendrite formation when cycled. The in-situ generated porosity dramatically increases the anode surface area and reduces dendrite formation by providing surface pores that fill with zinc as the anode is charged. In some aspects, the porosity improves cycle life without sacrificing capacity.
[0054] In any of the foregoing or following embodiments, the anode is (i) polarized in the range of 5 mV to 45 mV, or (ii) polarized at least 1 mAhcm -2 or (iii) an areal capacity of at least 500 mAhg -1 or (iv) any combination of two or more of (i), (ii), and (iii). In some embodiments, the polarization ranges from 5 mV to 35 mV, or from 5 mV to 25 mV. In some embodiments, the areal capacity is 1 mAhcm -2 ~15mAhcm -2 in the range of, for example, 2mAhcm -2 ~10mAhcm -2 , 4mAhcm -2 ~6mAhcm -2 , or 4.5mAhcm -2 ~5.5mAhcm -2 etc., corresponding to a depth of discharge of 45%. In some embodiments, the anode specific capacity is at least 550 mAhg -1 , at least 600mAhg -1 , or at least 700mAhg -1 , for example, anode specific capacity 500mAhg -1 ~770mAhg -1 , 600mAhg -1 ~770mAhg -1 , or 700mAhg -1 ~770mAhg -1 In one particular embodiment, the specific capacity of the full cell is 100 mAhg -1 ~120mAhg -1 , e.g. 105mAhg-1 ~115mAhg -1 In some embodiments, the anode exhibits stability over at least 250, at least 500, at least 600, or even at least 700 cycles. x M y Zinc z Alloy anodes (e.g., containing 8 at% to 15 at% indium) exhibit low polarization of about 5 mV to 45 mV and are 10 mA cm -2 The battery showed stability for over 700 cycles at a current density of 1000 and a depth of discharge of 45%.
[0055] In any of the foregoing embodiments, the anode may be prepared by electrodeposition or any other suitable method. Advantageously, electrodeposition may be cost-effective compared to high temperature alloy production, and may provide high yields, tunability, and / or scalability. In some embodiments, the In x M y Zinc z The alloyed film has an In:Zn molar ratio of x:z. 3+ ions and Zn 2+ It is formed by electrodeposition from an aqueous solution containing In ions. 3+ ions and Zn 2+ The ions may be provided by any water-soluble salt of In and Zn. In some embodiments, 3+ ions and Zn 2+The ions are provided by In2(SO4)3 and ZnSO4, respectively. In some embodiments, the aqueous solution further comprises an M cation. The M cation may be provided by any water-soluble salt of M. In some embodiments, the aqueous solution has an In:M:Zn molar ratio of x:y:z. In certain embodiments, the aqueous solution further comprises aluminum sulfate and boric acid. The deposition may be an alloy / metal-matrix deposition, which involves electrodeposition in the presence of particles that are convected into the deposited film. For example, Al may be deposited in the alloy by precipitation of Al2O3 due to a pH shift during the electrodeposition process. The alloy film may be electrodeposited onto a current collector. In some embodiments, a zinc layer (such as a layer having a thickness in the range of 0.5 μm to 1 μm) consisting of or containing primarily zinc in contact with the current collector may be deposited on the current collector first, as discussed above. Competitive zinc and indium deposition then occurs. Because indium is deposited more favorably, the concentration of indium may be higher in the lower region (closer to the current collector) of the deposited zinc-rich alloy compared to the overall indium concentration of the alloy. III. Rechargeable Zinc Cells
[0056] In some embodiments, the rechargeable zinc cell comprises an anode, a cathode, and an aqueous electrolyte as disclosed herein. The cell may further comprise a separator between the anode and the cathode.
[0057] In any of the above or following embodiments, the cathode may be any cathode suitable for use in a zinc cell with an aqueous electrolyte. The cathode may include a zinc insertion / intercalation material. In some embodiments, the cathode includes an organic electrode material. Suitable cathode materials include, but are not limited to, quinones, aromatic and anhydride imides, imines, metals, metal oxides, metal sulfides, metal organic frameworks (MOFs), Prussian blue, and Prussian blue analogs. In some embodiments, the cathode comprises dibenzo[b,i]thianthrene-5,7,12,14-tetraone (DTT), pyrene-4,5,9,10-tetraone (PTO), triangular phenanthrenequinone-based macrocycles (PQ-Δ), tetrachloro-1,4-benzoquinone (p-chloranil), tetraamino-p-benzoquinone (TABQ), 3,4,9,10-perylenetetracarboxylic diimide perylenediimide perylimide (PTCDI), 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA), phenazine (PXZ), or diquinoxalino[2,3-a:2′,3′-c]phenazine (HATN). Further suitable organic cathode materials can include polyaniline (PANI), polypyrrole (PPy), poly-thiophene (PTh), poly(3,4-ethylenedioxythiophene) (PEDOT), poly(p-phenylene) (PPP), polyindole (PIn), nitronyl nitroxide, organosulfur polymers, and triphenylamine and its derivatives. Suitable inorganic cathode materials include, but are not limited to, MnO2, vanadium oxide (VO x , e.g., V2O3, VO2, V2O5, V3O7), Zn x Mn 2-x O4 (wherein x≦1), MnS, Co3O4, Ag, MgV2O5, Bi2S3, calcium vanadium oxide (CaVO, e.g., CaV4O9, Ca 0.20 V2O5, Ca 0.67 V8O 20 etc.), Mn-based MOFs, Cu-based MOFs, Prussian Blue and the like. In some embodiments, the cathode comprises DTT.
[0058] In any of the above or following embodiments, the cathode may further include a current collector, one or more additives, and / or one or more binders. Suitable additives include carbon, such as acetylene black or graphite. Suitable binders include, for example, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), carboxymethyl cellulose, and cellulose acetate.
[0059] In any of the above or following aspects, the aqueous electrolyte may be any aqueous electrolyte suitable for use with a rechargeable zinc battery. In some aspects, the electrolyte comprises a zinc salt in water, such as a soluble zinc salt. Suitable zinc salts include, but are not limited to, ZnSO4, Zn(H2NSO3)2, Zn(CH3SO3)2, Zn(TFSI)2(Zn(C2F6NO4S2)2), Zn(FSI)2(Zn(F2NO4S2)2), Zn(ClO4)2, Zn(CH3CO2)2, and combinations thereof. In some embodiments, the electrolyte comprises aqueous zinc sulfate, such as 0.5M-3.5M ZnSO4, 0.5M-3M ZnSO4, 0.5M-2.5M ZnSO4, 0.5M-2M ZnSO4, or 1M-2M ZnSO4. In any of the above or following aspects, the electrolyte may be weakly acidic (e.g., pH 4-7).
[0060] In any of the preceding or following aspects, the rechargeable zinc battery has a capacity of at least 80 mAhg -1 , at least 90mAhg -1 , or at least 100mAhg -1 In some embodiments, the rechargeable zinc battery exhibits stability as evidenced by a constant or increasing specific capacity over at least 20 cycles, at least 30 cycles, or at least 40 cycles. In one embodiment, the rechargeable zinc battery comprises an In x Al y Zinc zA full cell having an anode, a DTT cathode, and an aqueous 2M ZnSO4 electrolyte provided a capacity of about 110 mAh g with excellent stability over 40 cycles (see, e.g., FIG. 12B, Example 2). In another example, cycling was performed at a current density of 1 mA cm and the corresponding charge was 5 mAh cm (correlating to a depth of discharge of 45%). The InAlZn anode of the symmetric cell showed a cycle life of at least 1000 hours (see, e.g., FIG. 9C, Example 2). At a high current density of 10 mA cm, the InAlZn anode showed a long cycle life of 700 hours (see, e.g., FIG. 10C, Example 2). -1 In another example, cycling was performed at a current density of 1 mA cm -2 and the corresponding charge was 5 mAh cm -2 (correlating to a depth of discharge of 45%). The In x Al y Zn z anode showed a cycle life of at least 1000 hours (see, e.g., FIG. 9C, Example 2). At a high current density of 10 mA cm -2 the In x Al y Zn z anode showed a long cycle life of 700 hours (see, e.g., FIG. 10C, Example 2). Exemplary embodiments
[0061] Certain exemplary embodiments are illustrated in the numbered paragraphs below.
[0062] 1. An anode comprising an InMZn alloy, wherein M is Al, Ag, Bi, Pb, Sn, Cd, or any combination thereof; when the anode has not been cycled previously, x ranges from 0.03 to 0.20; z ranges from 0.83 to 0.97; x + y + z = 1; the anode comprises indium domains and zinc domains distributed throughout the InMZn alloy; and the exposed upper surface of the anode has a zinc concentration of ≧ z. x M y Zn z alloy; when the anode has not been cycled previously, x ranges from 0.03 to 0.20; z ranges from 0.83 to 0.97; x + y + z = 1; the anode comprises indium domains and zinc domains distributed throughout the In x M y Zn z alloy; and the exposed upper surface of the anode has a zinc concentration of ≧ z.
[0063] 2. The anode of paragraph 1, wherein x ranges from 0.08 to 0.12; 0 < y ≦ 0.02; and z ranges from 0.86 to 0.92.
[0064] 3. The anode of paragraph 1 or paragraph 2, further comprising a current collector.
[0065] 4. The anode of item 3, further comprising a zinc layer having a thickness of 0.5 μm to 1 μm in contact with the current collector.
[0066] 5. In close proximity to the current collector x M y Zinc z The anode of term 3 or term 4, wherein the concentration of indium in the lower region of the alloy is >x.
[0067] 6. The anode, in a partially or fully discharged state after one or more cycles, has a porous surface portion including a plurality of pores, the porous surface portion having an indium concentration greater than x at% and a zinc concentration less than z at%; x M y Zinc z and a bulk portion comprising the alloy.
[0068] 7. The anode of item 6, wherein the porous surface portion contains at least 50 at % indium in a fully discharged state.
[0069] 8. The anode according to item 6 or 7, wherein the porous surface portion contains at least 75 at % indium in a fully discharged state.
[0070] 9. The anode of any one of paragraphs 6 to 8, wherein the porous surface portion comprises In2O3.
[0071] 10. The anode of any one of paragraphs 6 to 9, wherein the pores of the porous surface portion are at least partially filled with zinc when the anode is then in a partially or fully charged state.
[0072] 11. The anode of item 10, in which the morphology of indium at the porous surface portion remains stationary since the pores are filled with zinc during the charging process and are empty during the subsequent discharging process.
[0073] 12. (i) a polarization in the range of 5 mV to 45 mV; or (ii) at least 1 mAhcm -2 or (iii) an areal capacity of at least 500 mAhg. -1 or (iv) any combination of two or more of (i), (ii), and (iii).
[0074] 13. The anode of any one of paragraphs 1 to 12, wherein M is Al.
[0075] 14. A rechargeable zinc cell comprising: an anode of any one of paragraphs 1 to 13; a cathode; and an aqueous electrolyte.
[0076] 15. The cathode may be formed of dibenzo[b,i]thianthrene-5,7,12,14-tetraone, pyrene-4,5,9,10-tetraone, triangular phenanthrenequinone macrocycles, tetrachloro-1,4-benzoquinone, tetraamino-p-benzoquinone, 3,4,9,10-perylenetetracarboxylic diimide perylenediimide perylimide, 3,4,9,10-perylenetetracarboxylic dianhydride, phenazine, diquinoxalino[2,3-a:2',3'-c]phenazine, polyaniline, polypyrrole, poly-thiophene, poly(3,4-ethylenedioxythiophene), poly(p-phenylene), polyindole, nitronyl nitroxide, organic sulfur polymers, triphenylamine, triphenylamine derivatives, MnO2, vanadium oxide, Zn x Mn 2-x Item 15. The rechargeable zinc cell of item 14, comprising: O4 (wherein x≦1), MnS, Co3O4, Ag, MgV2O5, Bi2S3, calcium vanadium oxide, manganese-based metal-organic frameworks, copper-based metal-organic frameworks, Prussian blue, or a Prussian blue analogue.
[0077] 16. The rechargeable zinc cell of paragraph 14 or paragraph 15, wherein the aqueous electrolyte comprises ZnSO4, Zn(H2NSO3)2, Zn(CH3SO3)2, Zn(C2F6NO4S2)2, Zn(F2NO4S2)2, Zn(ClO4)2, and Zn(CH3CO2)2, or any combination thereof.
[0078] 17. The method of making the anode of any one of paragraphs 1 to 13, comprising the steps of: 3+ ions and Zn 2+ Electrodeposition from an aqueous solution containing In x M y Zinc z The method includes preparing a film including an alloy.
[0079] 18. The method of paragraph 17, wherein the aqueous solution further comprises an M cation.
[0080] 19. The method of claim 17 or 18, wherein the aqueous solution comprises In2(SO4)3 and ZnSO4.
[0081] 20. The method of any one of paragraphs 17 to 19, wherein the film is electrodeposited onto a current collector.
[0082] 21. The method of any one of paragraphs 17 to 20, wherein the aqueous solution further comprises aluminum sulfate and boric acid. EXAMPLES
[0083] V. Working Examples experiment
[0084] Copper and brass foils (0.254 mm thick, 99.9% Alfa Aesar on a metal basis) were used as current collectors for electrodeposition and subsequent symmetric and full cell testing. Brass was chosen as the substrate for InZn because indium is known to diffuse into copper during electrodeposition. The foils were then immersed in 10% sulfuric acid for 10 minutes to clean the surface, followed by immersion in Millipore water and then drying with argon.
[0085] The substrate foil was attached to a thick copper cathode (Koncour Company) by plating tape (3M) for constant current electrodeposition. Zinc anodes and platinized titanium sheet anodes were used for the electrodeposition of aluminum-zinc and indium-zinc films, respectively. Aluminum-zinc films were electrodeposited from a solution of 0.6 M ZnSO4 (99.9% Sigma Aldrich) + 30 g / L Al2(SO4)3 (97+% Alfa Aesar), and 0.5 M H3BO3 (99.97% Sigma Aldrich). Indium-zinc alloy films were electrodeposited from 0.6M ZnSO4 + 1.5M Na2SO4 (99% Sigma Aldrich) + 0.0125M, 0.025M, 0.037M In2(SO4)3 (98% Sigma Aldrich) + 0.5M H3BO3 + 30g / L Al2(SO4)3, and 0.01M saccharin (98% Sigma Aldrich) at 50 °C using magnetic stirring (ω = 1000 rpm). The zinc to indium molar ratio was 10:1 to ensure a zinc-rich alloy to bridge the reduction potential gap between indium and zinc (~0.35 V). The current density for the deposition of AlZn and InZn alloy anodes was 12.5 mA / cm, respectively. 2 and 25mA / cm 2 The target charge for both alloys was 12.5mAh / cm 2 After electrodeposition, all films were thoroughly rinsed with deionized water and dried under argon.
[0086] Commercially available zinc (90 wt%) anode powder was mixed with acetylene black (5 wt%) and 5 wt% polyvinylidene fluoride (PVDF) followed by planetary ball milling (Retsch PM 100 CM ball mill). The zinc powder film was then rolled onto a carbon-coated copper current collector and dried overnight at 120°C. The dried anode electrode film was then die-cut into a 0.625 inch diameter disk. The average mass loading of the zinc powder anode was approximately 12 mg / cm. 2 It was.
[0087] XRD measurements were performed using a Rigaku® Miniflex® II diffractometer using Cu Kα radiation (λ=1.5406 Å). SEM imaging was performed on a JEOL® JSM-7001F (field emission) scanning electron microscope (SEM) equipped with an Oxford EDX (energy dispersive X-ray) system with a silicon drift detector at 15 kV and 10 mm working distance. All cycled electrodes were carefully washed with water to remove electrolyte residues and dried in air before X-ray diffraction (XRD) and SEM analysis.
[0088] Zinc-based symmetric cells were tested in 2032-type coin cells under constant current conditions of 1 and 10 mA / cm 2 current density, 5mAh / cm 2 The cathodes were tested at a cut-off charge of 10 ... 2 Unless otherwise specified, for all full cells in these examples, 0.2C (0.57Ag -1 ) was used for constant current charge / discharge from 1.4 to 0.3 V. All electrochemical measurements were performed using a Biologic VMP3 multichannel potentiostat (Biologic USA) attached to a PC using EC-Lab software (v.11.3). Example 1 Anode preparation and characterization
[0089] Anodes of AlZn and InZn alloys were prepared by electrodeposition as described in the experimental section above, which involves electrodeposition in the presence of particles that are incorporated by convection into the depositing film. Incorporation of Al2O3 into Zn and InZn occurs by precipitation due to a pH shift during electrodeposition (Arakawa et al., Electrochemistry 2017 85(6):315-318).
[0090] Figures 2A-B, 3A-D, and 4A-B show the XRD spectra of electrodeposited AlZn, InZn, and commercial zinc foil. A side-by-side comparison shows that the commercial zinc foil (Figure 4A) has a prominent (101) lattice plane reflection peak at 43° 2θ (JCPDF#9012435), as well as nearly equal textural contributions of (100), (102), and (103) / (110) reflections. The electrodeposited (ED) AlZn film (Figure 2A) has the same reflections as the zinc foil, but with different relative intensities due to the (103) / (110) at 70° and the (102) reflection at 55°. There are no obvious peaks corresponding to either Al or Al2O3, since the concentration of Al2O3 is less than 1% according to the EDS data (see below). The InZn alloy exists as two distinct phases, with zinc (JCPDF (Joint Committee on Powder Diffraction Standard) #9012435) being the predominant phase, and indium (JCPDF #04-007-2066) (Figure 2B). Zinc and indium have virtually zero miscibility, so there are domains of indium surrounded by zinc. Both the AlZn and InZn alloys have diffraction peaks for the current collector (copper and brass, Cu 95 50° in AlZn alloys, associated with Zn5, and Cu 76 Zinc 24 75° in InZn alloys, which is associated with the high surface mobility (10 -8 ~10 -10 cm 2 s-1 ;Cao et al., Physical Review 1941, 59(4):376-381), which forms a surface alloy with Cu during the early stages of electrodeposition.
[0091] The surface morphology of the various anodes is shown in the scanning electron microscope (SEM) images in Figures 3A-3D. Unlike commercial zinc foil (shown in Figure 4B), which has a featureless surface with some macro-scratches and defects, the AlZn alloy (Figure 3A) is composed of hexagonal platelets stacked on top of each other. This is characteristic of electrodeposited zinc. Energy dispersive X-ray spectroscopy (EDX) analysis (Figure 3C) shows that it is composed mainly of zinc, with aluminum distributed uniformly throughout the surface. The atomic percentage of aluminum by EDX is less than 1 at%. Since the incorporation of aluminum into the zinc deposit is achieved by a precipitation mechanism, a low aluminum content is expected. In essence, the change in the local pH during the electrodeposition of zinc leads to the formation of Al2O3, which precipitates on the growing film and then becomes trapped as a new layer forms (Arakawa et al., Electrochemistry 2017 85(6):315-318). The InZn surface (Figure 3B) has some in common with AlZn in that the majority of the surface is composed of hexagonal platelets. However, the stacking / overlapping of these platelets is much more disordered compared to AlZn. An EDX scan of the surface (Figure 3D) shows that the surface is about 90 at% zinc with 10 at% indium and less than 1 at% aluminum. The Al in InZn is due to the presence of Al2(SO4)3 in the electrolyte of InZn deposition, which becomes trapped in InZn by the same mechanism as AlZn. The separated indium phase and the large domains of surrounded zinc confirm the separated phases of indium and zinc in the XRD of Figure 2B.
[0092] Transmission mode SEM (TSEM) analysis of the anode (Figures 5A-5D) at 10 mA cm -2The results were compared with the commercial zinc foil after the first discharge (Zn dissolution) (Figure 4C). The zinc foil changed from a relatively smooth surface (Figure 2B) to a highly defective surface covered with large pits (Figure 4C). This partly explains the tendency of zinc foil to form dendrites, since the surface inhomogeneity exacerbates the concentration gradient at the surface during subsequent deposition, leading to preferential deposition of zinc at the higher parts of the surface as nucleation points compared to the pitted areas. In contrast, the AlZn (Figure 5A) appeared almost identical to the original surface, albeit with some roughening. EDX analysis (Figure 5C) showed that the composition remained the same as the pristine surface, which was expected since the concentration of aluminum is constant throughout the AlZn film. The InZn characterized the most significant change in morphology, forming a porous network as shown in Figure 5B. EDX mapping (Figure 5D) shows that this network is composed of indium with zinc present underneath the pore spaces.
[0093] The amount of indium required to obtain this porosity was investigated by varying the indium concentration in the electrodeposition electrolyte. It was found that lowering the indium concentration in the solution by 50% reduced the surface concentration of indium to about 2-5 at% (for about 8-11 at% indium), which does not result in high porosity. Figures 6A-6D show SEM analysis of uncycled InAlZn with 2 at% surface indium (Figure 6A) and cycled 2 at% InAlZn (Figure 6B), as well as EDS mapping of uncycled 2 at% indium in InZn (Figure 6C) and cycled 2 at% indium in InZn (Figure 6D). In the anodes of Figures 6C and 6D, the electrodeposition electrolyte did not contain aluminum sulfate. It was found that increasing the indium concentration in the solution by 50% slightly increased the surface indium concentration (about 12 at%), but cyclability was poor due to the bulk containing 30 at% indium (Figures 7A-7F). It has been determined that an initial surface concentration in the range of 9.5 at% to 12 at% at the surface, corresponding to a bulk concentration in the range of 10 at% to 15 at% indium, provided superior results in certain embodiments. As can be seen in Figures 7D-7F, the first layer deposited on the current collector is zinc, followed by competitive deposition of zinc and indium. Since indium is more favored in deposition, the concentration of indium is higher in the lower portion of the deposited zinc-rich alloy compared to the overall indium concentration of the alloy.
[0094] Upon dealloying, the more noble component indium remained and rearranged / oxidized to result in a porous network. This is consistent with the formation of an In2O3 layer formed upon discharge of the galvanically exchanged indium-rich InZn, which allowed zinc to diffuse throughout the indium layer upon subsequent charging. This was evidenced in the low magnification EDX of the surface (Figure 8B), where higher oxygen concentrations were found in the indium-rich regions of the dealloyed surface. Example 2 Cells with InZn anodes
[0095] Symmetric cells were used to evaluate the feasibility of using the electrodeposited alloy as an anode in an aqueous zinc battery. -2 Practical capacitance limited to 1mAcm -2 ~10mAcm -2 The alloy zinc anodes were tested over a suitable current density range of about 0.1C to 1C. The cathode load in practical zinc cells is generally 5 to 10 mAhcm. -2 This means that the anode load will be approximately 20% higher, at 6 mAhcm -2 ~12mAhcm -2 These test conditions were chosen because they provide anode loads in the range of 0.5 mA cm2 and 1.0 mA cm2 depending on the cathode load and use case. -2 ~20mAcm -2 The range is (0.1C~4C).
[0096] 9A to 9C are plots of 1 mAcm -2 The cycles were performed at a current density of 5 mAhcm -2 The figures show a commercially available zinc foil, an AlZn anode, and an InZn anode with a capacity of 5 mAhcm. -2Charging corresponds to a depth of discharge (DOD) of 2.9% and 45% for the zinc foil and electrodeposited anodes, respectively. The zinc foil showed a polarization ranging from 30 mV to 40 mV, which was the highest among the anodes at a given current density compared to about 20 mV for the AlZn alloy and about 5 mV for the InZn alloy. Moreover, the commercial zinc foil was the least stable as the cell shorted after 130 h as shown in Figure 9A. The AlZn anode (Figure 9B) had a longer cycle life, reaching 225 h. The InZn anode not only showed the lowest cell polarization but also the longest cycle life of 1000 h (Figure 9C). It should be noted that in the experiments where the loading of the electrodeposited samples was low compared to the target loading, an asymmetric spike in polarization was observed. One possibility is that the asymmetric spike is associated with the high capacity moved during cycling. Further possibilities are due to the accumulation of indium on the surface, which changes the potential of the anode from that of pure zinc to that of an indium-rich surface, and / or exposure of the current collector due to uneven dissolution of the material.
[0097] 10mAcm -2 The results of anodes tested at high current densities of 100 mA cm are shown in Figures 10A-10C. Figure 10A shows that the polarization of the zinc foil increased to about 80 mV in conjunction with a decrease in stability when the cell was shorted after about 90 hours. The polarization of the AlZn anode (Figure 10B) increased to about 40 mV and the durability of the cell remained similar at 310 hours. The polarization of the AlZn anode increased asymmetrically to over 100 mV after 200 hours, which can be attributed to the uneven dissolution of AlZn causing exposure of the Cu current collector. Figure 10C shows the InZn symmetric cell, which showed an initial cell polarization of about 30 mV and increased at 500 hours due to the accumulation of indium on the surface of the electrode. However, even though the polarization increased, it was still below 10 mA cm. -2With a long cycle life of over 700 hours at a current density of 1000 mA, the InZn cell demonstrated significantly higher resistance to short circuiting of the cell. As shown in Figures 11A and 11B, anodes with indium concentrations above 15 at% (Figure 11A) or below 5 at% (Figure 11B) showed reduced cycle life compared to the InZn anode of Figure 10C.
[0098] The InZn anode was further evaluated in a full cell combined with a DTT cathode in 2M ZnSO4. These full cells with various anodes (Zn foil, AlZn, and InZn) had similar charge / discharge curves, and Figure 12A shows a typical charge / discharge curve of DTT with zinc foil. The discharge plateau at about 0.75 V and the charge plateau at about 0.99 V indicate the H in the DTT structure. + This is due to the insertion and extraction of ZnO (Wang et al., Adv. Mater. 2020, 32(16):2000338). Full cells with AlZn and InZn anodes showed similar cycling stability as the commercial zinc foil anode (Figure 12B), indicating that both AlZn and InZn perform as well as zinc foil but have better resistance to dendrite formation as shown in the symmetric cell test. -1 ) and the difference in capacity between the electrodeposited anode (130 mAg -1 AlZn vs 110mAg -1 The AlZn and InZn anodes were compared in zinc foil cells (5 mg cm) which could be attributed to alloying elements and / or cathodic loading, which slightly change the anode potential compared to pure zinc. -2 ) with a slightly higher load (6 mg cm -2 ), which results in lower capacity until the cathode is fully wetted.
[0099] The InZn anodes showed better dendrite mitigation and electrochemical performance than AlZn alloys, mainly due to the controlled indium doping, which allows the formation of a unique porous structure upon dealloying. Without wishing to be bound by a particular theory of operation, the indium domains rearrange upon dealloying to form connected walls of the porous structure, and the structure is stabilized after the formation of an oxide on the surface. The formation of the porous structure is related to the indium level. The results shown in FIG. 8B are for an anode with 10 at.% indium. With an indium concentration as low as 2 at.%, the porous structure almost disappeared (FIGS. 6A-6D), because the Al2O3 / Zn alloy formed by electrodeposition did not reach a high enough indium concentration in the surface area to form a porous structure (FIGS. 6A-6D). Notably, commercial zinc particles doped with very low concentrations of indium (e.g., 300 ppm, <1.7 at.% indium) to minimize gassing do not form a porous structure when cycled (FIGS. 13A, 13B).
[0100] The results demonstrate that InZn anodes with zinc domains surrounding indium domains form a porous structure to mitigate dendritization, resulting in high capacity utilization and long-term cycling stability at high current densities. The InZn alloy anodes showed much lower polarization in symmetric cells with zinc foil or AlZn anodes. Compared to many energy-intensive nanosynthetic routes, electrodeposition is cost-effective, has high yields, is tunable, and is easily scalable.
[0101] In view of the many possible embodiments to which the principles of the disclosed invention may be applied, the illustrated embodiments should be recognized as merely preferred examples of the invention and should not be taken as limiting the scope of the invention. Rather, the scope of the invention is defined by the following claims. The inventors therefore claim as their invention all that comes within the scope and spirit of these claims.
Claims
1. In x M y Zinc z An anode comprising an alloy, M is Al, Ag, Bi, Pb, Sn, Cd, or any combination thereof; If the anode has not been previously cycled, x ranges from 0.03 to 0.20; z is in the range of 0.83 to 0.97; x+y+z=1; The anode is x M y Zinc z including indium domains and zinc domains distributed throughout the alloy; the exposed top surface of the anode has a zinc concentration ≧z; anode.
2. x is in the range of 0.08 to 0.12; 0<y≦0.02; z is in the range of 0.86 to 0.92; 2. The anode of claim 1.
3. 10. The anode of claim 1 further comprising a current collector.
4. 4. The anode of claim 3, further comprising a zinc layer in contact with the current collector and having a thickness of 0.5 μm to 1 μm.
5. The In adjacent to the current collector x M y Zinc z 4. The anode of claim 3, wherein the concentration of indium in the lower region of the alloy is >x.
6. In a partially or fully discharged state after one or more cycles, the anode a porous surface portion comprising a plurality of pores, the porous surface portion having an indium concentration greater than x at% and a zinc concentration less than z at%; The In x M y Zinc z A bulk portion containing an alloy and 2. The anode of claim 1 comprising:
7. 7. The anode of claim 6, wherein said porous surface portion comprises at least 50 at % indium in said fully discharged state.
8. 8. The anode of claim 7, wherein said porous surface portion comprises at least 75 at % indium in said fully discharged state.
9. The porous surface portion is In 2 O 3 7. The anode of claim 6 comprising:
10. 7. The anode of claim 6, wherein the pores of the porous surface portion are at least partially filled with zinc when the anode is then in a partially or fully charged state.
11. 11. The anode of claim 10, wherein the morphology of indium at the porous surface portion remains stationary as the pores are filled with zinc during a charging process and subsequently vacant during a discharging process.
12. The anode is (i) a polarization in the range of 5 mV to 45 mV; or (ii) at least 1 mAh cm -2 or (iii) at least 500 mAhg -1 specific capacity; or (iv) any combination of two or more of (i), (ii), and (iii).
2. The anode of claim 1 having the following structure:
13. 2. The anode of claim 1, wherein M is Al.
14. An anode according to any one of claims 1 to 13; A cathode; Aqueous electrolytes and Includes a rechargeable zinc cell.
15. The cathode may be any of the following: dibenzo[b,i]thianthrene-5,7,12,14-tetraone, pyrene-4,5,9,10-tetraone, triangular phenanthrenequinone-based macrocycles, tetrachloro-1,4-benzoquinone, tetraamino-p-benzoquinone, 3,4,9,10-perylenetetracarboxylic diimide perylenediimide perylimide, 3,4,9,10-perylenetetracarboxylic dianhydride, phenazine, diquinoxalino[2,3-a:2',3'-c]phenazine, polyaniline, polypyrrole, poly-thiophene, poly(3,4-ethylenedioxythiophene), poly(p-phenylene), polyindole, nitronyl nitroxide, organosulfur polymers, triphenylamine, triphenylamine derivatives, MnO 2 , vanadium oxide, Zn x Mn 2-x O 4 (in the formula, x≦1), MnS, Co 3 O 4 , Ag, MgV 2 O 5 , Bi 2 S 3 15. The rechargeable zinc cell of claim 14, comprising: calcium vanadium oxide, manganese-based metal-organic frameworks, copper-based metal-organic frameworks, Prussian blue, or a Prussian blue analog.
16. The aqueous electrolyte is ZnSO 4 , Zn(H 2 NSO 3 ) 2 , Zn(CH 3 SO 3 ) 2 , Zn(C 2 F 6 NO 4 S 2 ) 2 , Zn(F 2 NO 4 S 2 ) 2 , Zn(ClO 4 ) 2 , and Zn(CH 3 CO 2 ) 2 15. The rechargeable zinc cell of claim 14, comprising:
17. 14. A method for making the anode of claim 1, comprising the steps of: 3+ ions and Zn 2+ The In was deposited by electrodeposition from an aqueous solution containing ions. x M y Zinc z The method includes preparing a film including an alloy.
18. The aqueous solution is In 2 (SO 4 ) 3 and ZnSO 4 20. The method of claim 17, comprising:
19. The method of claim 17 , wherein the film is electrodeposited onto a current collector.
20. 20. The method of claim 17, wherein the aqueous solution further comprises aluminum sulfate and boric acid.
Citation Information
Patent Citations
High current alkaline zinc-manganese battery using superfine alloy zinc powder
CN106129379A
battery
JP1990177269A
Zinc alloy powder for battery
JP2005100945A
Button type alkaline battery
JP2005259395A
Electrode for air secondary battery, and air secondary battery
JP2014053198A